DISTRIBUTION OF 86RUBIDIUM AND METIONINE 75SELENIUM IN ORGANS OF RATS AFTER EXERCISE AND TREATMENT WITH PROTEIN HYDROLYZATE AND VITAMIN C - Miroslav Marinov; Iglika Marinova; Christiana Romanova; Nina Radeva; Borislav Boychev; M. Panteleeva; Kosta Mirchev; Radko Zl. Radev (Peytchinski Publishing, 2013)
Purpose of the study is to track in, the blood flow and the metabolism in 15 organs of experimental rats, which are subjected to severe physical strain, treated with protein hydrolyzate and vitamine C (Vit. C). The animals are divided into one control and 4 experimental groups. After 30 minutes of swimming they are treated with already used produces, methionine 75selenium and and after another 2 hours of swimming, with 86rubidium. After being euthanized with thiopental and an autopsied, the following organs are taken from the rats: pancreas, spleen, testicles, duodenum, a part of small intestine and colon, adrenals, kidneys, liver, lungs, heart, aorta, a piece of muscle, part of a brain and stomach. Percentage of the activity per gram of tissue is determined, of the total activity, of the two isotopes for every organ and them being compared. Physical strain deteriorates blood flow and reduces the accumulation of methionine 75selenium, while the treatment with the hydrolyzate and Vit. C has a beneficial effect in almost all organs.